Efeito dos treinamentos multicomponente e mat pilates na marcha em solo instável de indivíduos com Doença de Parkinson: um ensaio clínico randomizado-controlado unicego - Dorasio, Ana Cláudia Pamplona (2019)
Introduction: Parkinson's disease (PD) is a chronic, progressive, degenerative disease of the central nervous system with multifactorial etiology. Changes in gait patterns and postural control in these individuals are responsible for a high incidence of falls and severe injuries. Physical exercise is an important tool for rehabilitation and maintenance of the functionality and mobility of individuals with PD. Objective: To compare the effects of Multicomponent Training (MT) and Mat Pilates (MP) on gait performance in unstable ground according to temporal kinematic variables of individuals with PD. Methods: Twenty-two individuals with idiopathic Parkinson's disease were randomized and allocated to two intervention groups: TM and PM. Interventions were performed in a 60-minute group with a frequency of three times a week for 12 weeks. The kinematic assessment of gait was performed before and after the intervention protocol, using footswitch pressure sensors positioned at the base of the hallux and calcaneus to determine gait cycles. In this study, the cadence, balance time, double support time, stride time and speed were evaluated. Results: We used the Generalized Estimation Equations (GEE) model and verified the significant effect of the time x group interaction on the cadence variable (p=0.02). Regarding the effect of time, after 12 weeks of intervention, a significant increase in velocity was found in both groups (TM: p=0.001; MP: p<0.001), increase in cadence (p=0.04) and pass time (p=0.039) in the TM group. Conclusion: Both interventions have positive effects on gait speed. However, the spatio-temporal adjustments made to achieve the speed increase seem to have been better in the Mat Pilates group, considering the PD progression characteristics.